The role of reward-based crowdfunding in farm financing: What characterises successful campaign? - Ljumović Isidora (Naučno društvo agrarnih ekonomista Balkana, Beograd; Institut za ekonomiku poljoprivrede, Beograd i Akademija ekonomskih nauka, Bukurešt, 2021)
The purpose of this paper is to provide insight into the role of reward-based crowdfunding in farm financing, with a focus on its likelihood of success. The study uses a sample of 1,566 projects from the Kickstarter platform between 2014 and 2020. We added the level of urbanisation and relative importance of agriculture in the country's economy to the basic elements to assess the importance of the crowdfunding. We run a logistic regression model to investigate factors that motivate investment decisions. We discovered a statistically significant negative correlation between the self-set campaign goal and project success, as well as a small positive impact of number of backers and a positive impact of the importance of agriculture in the country's economy on crowdfunding success. In an era of rapid innovation and the rise of social networks, this paper contributes to the current literature on the agri-food industry's reword-based crowdfunding approach.